Iodoargentate/iodobismuthate-based materials hybridized with lanthanide-containing metalloviologens: thermochromic behaviors and photocurrent responses. Issue 5 (28th March 2018) - Wang, Dao-Hua; Zhao, Li-Ming; Lin, Xiao-Yan; Wang, Yu-Kang; Zhang, Wen-Ting; Song, Kai-Yue; Li, Hao-Hong; Chen, Zhi-Rong
Abstract : New hybrids combined metalloviologens with Ag/Cu iodides exhibit reversible thermochromisms, photocurrent responses, whose mechanisms are disclosed. Abstract : Two new types of iodoargentate/iodobismuthate-based inorganic–organic hybrids were prepared and structurally characterized as {[Ln2 (dpdo)(DMF)14 ](Ag12 I18 )} n (bpdo = 4, 4′-bipyridine N, N ′-dioxide, Ln = La (1 ), Nd (2 ), Sm (3 )) and {[Ln(dpdo)(DMF)6 ](Bi2 I9 )2 } n (Ln = La (4 ), Pr (5 ), Er (6 )). These lanthanide–silver/bismuth heterometallic hybrids feature the novel templates of lanthanide-containing metalloviologen analogs, i.e., [Ln2 (dpdo)(DMF)14 ] 6+ (dimers for1–3 ) and [Ln(dpdo)(DMF)6 ] n 3 n − (1-D chains for4–6 ). The (Ag12 I18 ) n 6 n − chains in1–3 are constructed from edge-sharing Ag6 I12 units, and (Bi2 I9 ) 3− clusters in4–6 are defined by two face-sharing BiI6 otcahedra. The versatile weak interactions between metalloviologens and metal iodides stabilize the structures. Upon the introduction of metalloviologens, reversible thermochromism can be found in1–6 . Besides, electrodes with films of1–6 exhibit effective and repeatable photocurrent responses. Finally, the possible thermochromism and photocurrent response mechanisms are also discussed.